Uncanny bodies : superhero comics and disability - Smith, Scott Thompson; Alaniz, José (Graphic medicine., 2019)
"Superhero comics reckon with issues of corporeal control. And while they commonly deal in characters of exceptional or superhuman ability, they have also shown an increasing attention and sensitivity to diverse forms of disability, both physical and cognitive. The essays in this collection reveal how the superhero genre, in fusing fantasy with realism, provides a visual forum for engaging with issues of disability and intersectional identity (race, ethnicity, class, gender, and sexuality) and helps to imagine different ways of being in the world. Working from the premise that the theoretical mode of the uncanny, with its interest in what is simultaneously known and unknown, ordinary and extraordinary, opens new ways to think about categories and markers of identity, Uncanny Bodies explores how continuums of ability in superhero comics can reflect, resist, or reevaluate broader cultural conceptions about disability. The chapters focus on lesser-known characters--such as Echo, Omega the Unknown, and the Silver Scorpion--as well as the famous Barbara Gordon and the protagonist of the acclaimed series Hawkeye, whose superheroic uncanniness provides a counterpoint to constructs of normalcy. Several essays explore how superhero comics can provide a vocabulary and discourse for conceptualizing disability more broadly. Thoughtful and challenging, this eye-opening examination of superhero comics breaks new ground in disability studies and scholarship in popular culture."--Provided by publisher